Opportunities of Water Extracts of Sorghum Main and Ratoon Plants with Their Organs as Bioherbicides - Edi Susilo; Parwito; Dia Novita; Eny Rolenti Togatorop; Tatik Raisawati; Susi Handayani; Andreani Kinata; Hesti Pujiwati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sorghum is a multipurpose crop used as food, feed, organic fertilizer, and bioherbicide. Water extracts from main and ratoon plants with leaf, stem, and root organs produced in swamplands as bioherbicides are interesting topics to research. The research aims to determine the potential of water extracts from main and ratoon plants with leaf, stem, and root organs produced in swamplands as bioherbicides. The research was conducted from November 2020 to May 2021 (stalk preparation) and October 2022 (bioassay test) in Bentiring Permai, Muara Bangkahulu, Bengkulu City. This research applied a randomized group design. The bioassay experiment was arranged factorially with two factors. The first factor is the type of plant, with two levels, namely the main plant and the ratoon plant. The second factor is the source of the extract, with three levels: leaves, stems, and roots. The experiment was repeated four times, and the experimental unit was a petri dish. Each petri dish was given 10 ml of water extract, planted 25 sorghum seeds of the Suri 3 variety were incubated for four days. The results showed a diversity of plant species and organs in producing allelopathy. Water extracts derived from ratoon plant stems and main plant roots produce good inhibition, so they have the potential to be the best bioherbicide